An Assesment of the Significance of Adaptive Reuse Focused Design Studio in Interior Design Education - Jahromi, Faraneh Sahraiyan (Eastern Mediterranean University EMU, 2015)
Adaptive reuse, which indicates the functional and physical changes of a building mainly with a historical value, has become an important part of interior architectural practices. Conserving the heritage buildings and their cultural value for future generations present a real challenge for professional education programs, which are responsible for training young experts who can focus on the aspects of architectural heritage conservation. However, there is minimal research attention, which is directed towards adaptive reuse as an integral part of learning in interior architectural education. The main issue of this paper is to lessen this gap. Meanwhile, research on learning architectural heritage conservation can offer an opportunity to involve student views as a main data source and hence better understand the conceptions and misconceptions that the students hold about adaptive reuse in the interior design studio. With this understanding, this study, analyzes and evaluates the role of integrating adaptive reuse concept to learning in the interior architectural design studio and ascertain the value of such an approach as a contribution to heritage conservation awareness rising. Keywords: Architectural heritage conservation, Adaptive reuse, Learning adaptive reuse, Interior architecture, Design studio

ÖZ: Tarihi değeri olan bir binaya yapılan işlevsel ve fiziki değişikliklere işaret eden “yeniden kullanım” son zamanlarda iç mimarlık uygulamalarının da önemli bir parçası haline gelmiştir. Mesleki eğitim veren birçok yüksek öğrenim kurumu için, koruma konularına odaklanabilen genç uzmanlar yetiştirebilmek; kültürel mirasımızın korunabilmesi ve gelecek nesillere aktarılabilmesi açısından önemli bir ödev ve sorumluluktur. Buna rağmen, iç mimarlık eğitiminde, yeniden kullanım kuramlarının öğrenimin entegre bir parçası olmasının önemine ve gereğine işaret eden çok az araştırma vardır. Bu çalışmanın esas hedefi, bu eksikliği biraz olsun gidermektir. Ayni zamanda, bu çalışma, kültürel mirası koruma eğitimi üzerine yapılan araştırmalara öğrenci bakış açısını da, önemli bir bilgi kaynağı olarak katmak bağlamında güzel bir olanaktır. Bu sayede, öğrencilerin iç mekan tasarımı eğitimleri çerçevesinde yeniden kullanım konuları ile ilişkili olark edindikleri doğru veya yanlış fikirler ve bilgiler gün ışığına çıkabilecektir. Bu bakış açısı ile kurgulanmış olan bu çalışma, yeniden kullanım konseptinin entegre edildiği bir iç mimarlık tasarım stüdyosunu mercek altına alıp analiz eder, değerlendirmelerde bulunur ve kültür mirasımızı koruma farkındalığına nasıl bir koyduğunu irdeler. Anakatar Kelimeler: Mimari kültürel mirası koruma, Yeniden kullanım, Yeniden kullanım öğrenimi, İç mimarlık, Tasarım stüdyosu
Master of Science in Interior Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2015. Supervisor: Assist. Prof. Dr. Münevver Özgür Özersay.
Keywords: Interior Architecture; Interior Design; Historic buildings-Remodeling for other use; Buildings-Repair and reconstruction; Architecture-Conservation and restoration; Architectural heritage conservation; Adaptive reuse; Learning adaptive reuse; Interior architecture; Design studio